Nuankaew, S., Chuaseeharonnachai, C., Somrithipol, S., Kwantong, P., Srihom, C., Ros, C. & Boonyuen, N. (2021) Contribution to Chaetosphaeriaceae—Kionochaeta setosimplicia sp. nov. from Thailand. Phytotaxa 508 (2): 175–186. - Nuankaew, Salilaporn (Phytotaxa, 2021)
N/A